EFEKTIVITAS MEDIA WORDWALL DALAM MENINGKATKAN PENGUASAAN QAWA’ID PADA SISWA MA DARUL ULUM TLASIH TULANGAN SIDOARJO - Nia Fatma Safitri; Najih Anwar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effectiveness of the wordwall media in improvingstudents’ mastery of qawa’id (arabic grammar) among 10th-grade students at MADarul Ulum Tulangan Sidoarjo. The problem identified is the students’ lowcomprehension of qawa’id due to the reliance on conventional teaching methodsand the lack of engaging media. A quantitative research method was employedusing a pre-experimental design (One-Group Pre-Test Post-Test Design) involving31 students selected through a census sampling technique. Research instrumentsincluded tests (pre-test and post-test), interviews, observations, and documentation.The wordwall media used consisted of quiz, unjumble, and open the box formats.The descriptive statistical analysis showed a significant improvement in students’learning outcomes, with an average pre-test score of 40.94 and a post-test score of89.65. The paired sample t-test revealed a significance value (2-tailed) of 0.000 (<0.05), indicating a statistically significant difference before and after using thewordwall media. Therefore, it can be concluded that wordwall is effective inenhancing students’ mastery of qawa’id.